Emotional intelligence implications in health and emotional welfare - Martínez González, Agustín Ernesto (2009)
In this article, we have tried to group the results from different researches related to EI and physic and mental health. One of the conclusions we have is that EI perceived through report (TMMS, etc.) as well as EI executed (MSCEIT) are related to people’s health and welfare. Likewise, the average of MSCEIT grades for different clinic groups of people (schizophrenia, AIDS, Depression, etc.) and non - clinic groups of people(university students, students, etc), give us a vision of psychopathology- normal continuum, being the highest grades in EI of MSCEIT the ones which are positively related to personal health and stable emotional state.